2009
DOI: 10.1002/pola.23372
|View full text |Cite
|
Sign up to set email alerts
|

Prepolymerization and postpolymerization functionalization approaches to fluorescent conjugated carbazole‐based glycopolymers via “click chemistry”

Abstract: Facile prepolymerization and postpolymerization functionalization approaches to prepare well‐defined fluorescent conjugated glycopolymers through Cu(I)‐catalyzed azide/alkyne “Click” ligation were explored. Two well‐defined carbazole‐based fluorescent conjugated glycopolymers were readily synthesized based on these strategies and characterized by 1H NMR, 13C NMR, IR spectra, and UV‐vis spectra. The “Click” ligation offers a very effective conjugation method to covalently attach carbohydrate residues to fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Both photochemical and thermal radical conditions were tested to explore the efficiency of the thiol‐ene reaction, and it was found that using photochemical conditions leads to faster and, in many cases, quantitative reaction. The authors also verified the orthogonality of thiol‐ene with copper catalyzed azide‐alkyne cycloaddition (CuAAC) 43–45. Ma et al studied a series of monomers containing alkenes and their usage for the synthesis of homopolymers, block copolymers, and random copolymers 46.…”
Section: Introductionmentioning
confidence: 88%
“…Both photochemical and thermal radical conditions were tested to explore the efficiency of the thiol‐ene reaction, and it was found that using photochemical conditions leads to faster and, in many cases, quantitative reaction. The authors also verified the orthogonality of thiol‐ene with copper catalyzed azide‐alkyne cycloaddition (CuAAC) 43–45. Ma et al studied a series of monomers containing alkenes and their usage for the synthesis of homopolymers, block copolymers, and random copolymers 46.…”
Section: Introductionmentioning
confidence: 88%
“…We have reported the synthesis of various FCPs with pendant carbohydrates and their interactions with lectins or DNA 27–29. To extend the potential application of FCPs in chemo‐ and biosensing, herein, two well‐defined triphenylamine‐based conjugated polymers containing terpyridyl ligands were synthesized (Scheme ) and well characterized using 1 H‐NMR, 13 C‐NMR, Infrared (IR), and UV‐vis spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Using those methods, triphenylamine-based conjugated glycopolymers were prepared for studies of specific carbohydrate-lectin interaction. [15] However, positively charged fluorescent conjugated glycopolymers for detecting polyanions based on electrostatic interaction have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…With high efficiencies in both photoluminescence and electroluminescence, polyfluorene derivatives have gained much attention during the past decade as versatile active materials in optoelectronic devices and fluorescent sensory materials. [16] In this communication, cationic water-soluble conjugated polyfluorene with pendant glucosamine hydrochloride (P-2) was easily synthesized through the prepolymerization functionalization approach, [14] which is based on Cu(I)-catalyzed azide/ alkyne ''click'' ligation [17] and Suzuki coupling polymerization. The preliminary study of P-2-single-stranded DNA (ssDNA) interaction was performed by a series of spectrofluorometric titration.…”
Section: Introductionmentioning
confidence: 99%